Managing Records as an Information Governance Initiatives: Preliminary Study - Novian, Rayhan Musa (Universitas Pendidikan Indonesia, 2023)
Information is vital for organisations. Every administrative action conducted within the scope of the organisation should incorporate information. The qualitative method was linked with the exploratory case study technique. This strategy was chosen due to the study time required to evaluate the present circumstances of the Library and Record Municipal Office of Batam City. Based on the study, records management as the initiation of information governance in information institutions, namely the library and records office of Batam City, is still not running well. There are still implementation problems, such as procuring a record centre for in-active record management. Suppose the procurement of record centre facilities is held. In that case, problems such as in-active record management, media transfer and record retention entering the time of destruction will not occur.